1999
DOI: 10.1097/00003246-199910000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative evaluation of tissue perfusion in high-risk patients by invasive and noninvasive hemodynamic monitoring

Abstract: The survivors had slightly higher mean arterial pressure, cardiac index, and mixed venous oxygen saturation, as well as significantly higher oxygen delivery, oxygen consumption, transcutaneous oxygen tension, and transcutaneous oxygen tension/FIO2 ratios, than did the nonsurvivors. The data suggest that blood flow, oxygen delivery, and tissue oxygenation of the nonsurvivors became inadequate toward the end of the operation. Noninvasive monitoring provides similar information to that of the PAC; both approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 35 publications
0
18
0
4
Order By: Relevance
“…5,9,[16][17][18] Conversely, excessive fluid restriction, especially using unmonitored and fixed volumes, may expose a patient's tissue to hypovolemia and hypoperfusion, which are key triggers of organ dysfunction. 3,[19][20][21] Nevertheless, maintenance of the volume of intravascular fluid is essential to ensure adequate organ per-fusion. Surgical trauma is associated with endothelial damage arising from mechanical stress, endotoxin exposure, ischemia-reperfusion injury, or inflammation, 5,22 all of which can lead to increased endothelial permeability and unpredictable extravascular fluid shifts.…”
mentioning
confidence: 99%
“…5,9,[16][17][18] Conversely, excessive fluid restriction, especially using unmonitored and fixed volumes, may expose a patient's tissue to hypovolemia and hypoperfusion, which are key triggers of organ dysfunction. 3,[19][20][21] Nevertheless, maintenance of the volume of intravascular fluid is essential to ensure adequate organ per-fusion. Surgical trauma is associated with endothelial damage arising from mechanical stress, endotoxin exposure, ischemia-reperfusion injury, or inflammation, 5,22 all of which can lead to increased endothelial permeability and unpredictable extravascular fluid shifts.…”
mentioning
confidence: 99%
“…[8][9][10][11] One study found that the magnitude of the tissue organ debt perioperatively was related to the subsequent development of organ failure and death. 11 Tissue hypoxia is a potent stimulus for an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…These datasets have been used in several focused studies conducted in the past at LAC+USCMC [e.g., Refs. [6][7][8][9][10][11]. The percentage of patients covered by various physiological parameters is presented in Table 3 to help characterize the sensor coverage.…”
Section: Main Project Databasementioning
confidence: 99%